2022
DOI: 10.1016/j.xcrm.2021.100497
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine enhances caveolar transport of therapeutic agents across the rodent blood-brain barrier

Abstract: Summary The blood-brain barrier (BBB) restricts clinically relevant accumulation of many therapeutics in the CNS. Low-dose methamphetamine (METH) induces fluid-phase transcytosis across BBB endothelial cells in vitro and could be used to enhance CNS drug delivery. Here, we show that low-dose METH induces significant BBB leakage in rodents ex vivo and in vivo . Notably, METH leaves tight junctions intact and induces transient leakag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The effect of methamphetamine on BBBD is not observed in the caveolin-1 knockout mouse [272]. Methamphetamine, a highly addictive drug of abuse, has been recently suggested as a new brain drug delivery strategy [272], which follows the original suggestion of this idea made by Kast in 2007 [273]. The methamphetamineinduced formation of reactive oxygen species in cultured endothelium is blocked by the anti-oxidant, N-tertbutyl-α-phenylnitrone (PBN) [274].…”
Section: Bbbd and Free Radicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of methamphetamine on BBBD is not observed in the caveolin-1 knockout mouse [272]. Methamphetamine, a highly addictive drug of abuse, has been recently suggested as a new brain drug delivery strategy [272], which follows the original suggestion of this idea made by Kast in 2007 [273]. The methamphetamineinduced formation of reactive oxygen species in cultured endothelium is blocked by the anti-oxidant, N-tertbutyl-α-phenylnitrone (PBN) [274].…”
Section: Bbbd and Free Radicalsmentioning
confidence: 99%
“…Methamphetamine causes BBBD in association with the formation of free radicals, and the effect on the BBB is attenuated by Trolox, an anti-oxidant water-soluble analogue of vitamin E [271]. The effect of methamphetamine on BBBD is not observed in the caveolin-1 knockout mouse [272]. Methamphetamine, a highly addictive drug of abuse, has been recently suggested as a new brain drug delivery strategy [272], which follows the original suggestion of this idea made by Kast in 2007 [273].…”
Section: Bbbd and Free Radicalsmentioning
confidence: 99%
“…8 shows the abundance of caveolin 1 in M30 in comparison with DD90, indicating caveolae induction. For the prospect of gene delivery across the BBB, we reckon the particles that could be used in combination with agonist-induced models of caveolae induction 36 or with physical methods like low-dose ultrasound. 38…”
Section: M30 and Caveolae-mediated Endocytosismentioning
confidence: 99%
“…35 New strategies that employ caveolae-mediated transcytosis as a means to deliver drugs to the brain using both chemical and physical techniques have been developed. 36–38 Caveolae, which are preformed vesicles ranging from 80 to 100 nm, are invaginations found in the plasma membrane and play a role in size-dependent endocytosis. 39 However, sugar alcohol modification leads to an increase in the size of the nanoparticles as reported with plasmid DNA (pDNA).…”
Section: Introductionmentioning
confidence: 99%
“…Upon activation, Cav-1 undergoes a conformational change that triggers membrane curvature and formation of intracellular vesicles that contain cargos (Ohi & Kenworthy, 2022; Zimnicka et al, 2016). Suppression of brain endothelial cell Cav-1 is a key mechanism of BBB development, and loss of Cav-1 causes transcellular BBB permeability (Andreone et al, 2017; Chang et al, 2022; Chow & Gu, 2017; Wang et al, 2020). We and others have shown that Cav-1-related vesicular trafficking is normally maintained at low levels in mature brain EC but is upregulated in neuroinflammation in vivo (Knowland et al, 2014; Lutz et al, 2017; Salimi et al, 2020; Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%